2021
DOI: 10.52965/001c.28362
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Reliability of Carbon-Peek Plate for the Treatment of Distal Radius Fractures: A Review of the Literature

Abstract: IntroductionDistal radius fractures are one of the most common injuries. Open reduction and internal fixation (ORIF) are the most diffused between surgical treatments. Carbon-fiber reinforced (CFR) polyetheretherketone (PEEK) plates have been proposed to prevent effects linked to stainless steel or titanium alloy traditional plates, such as radio-opacity, mismatch of bone-plate elasticity modulus, corrosion, limited fatigue life, osseointegration. ObjectiveThis review aims to evaluate the actual safety and rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Three systematic reviews have previously evaluated CF plates for trauma fracture fixation. Firstly, Saracco et al included seven studies on distal radius fractures, and reported CF as a potential alternative to conventional metal plates [ 12 ]. Secondly, Theivendran et al evaluated CF fixation in a broader population with small improvements in functional recovery of CF plates after humerus fractures, while there was insufficient evidence to support its widespread use [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Three systematic reviews have previously evaluated CF plates for trauma fracture fixation. Firstly, Saracco et al included seven studies on distal radius fractures, and reported CF as a potential alternative to conventional metal plates [ 12 ]. Secondly, Theivendran et al evaluated CF fixation in a broader population with small improvements in functional recovery of CF plates after humerus fractures, while there was insufficient evidence to support its widespread use [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Robust clinical studies and evidence are warranted for comprehensive knowledge regarding safety, complication, and long-term outcome of these implants. [32] 3D Printed Plates 3D printing or rapid prototyping or additive manufacturing, has revolutionized many sectors and the bespoke implant manufacturing is an emerging arena. 3D printers convert images into physical models on 3D digital imaging and communication in medicine format data abstracted from CT or MRI through additive manufacturing.…”
Section: Rib Platesmentioning
confidence: 99%
“…At present, PEEK implants are increasingly used as spinal cages [ 4 ], skull or maxillofacial defect repair implants [ 5 , 6 ], dental implants [ 7 ], joint replacements [ 8 ], fixation devices [ 9 ], and so on. PEEK cages are widely used in spinal fusion due to their radiolucency and low elastic modulus [ [10] , [11] , [12] ].…”
Section: Introductionmentioning
confidence: 99%
“…These metal devices suffer from radiation opacity, elastic modulus mismatch, corrosion, limited fatigue life, susceptibility to cold welding of plates and screws, and osseointegration [ 35 , 36 ]. Because CFR-PEEK can improve these shortcomings [ 37 ], some researchers apply CFR-PEEK to fracture repair [ 9 , 38 ]. However, a comparative study pointed out that the disadvantage of CFR-PEEK relative to metal plates is the low tolerance for plastic deformation and the risk of fracture [ 37 ].…”
Section: Introductionmentioning
confidence: 99%